Knowledge about HIV transmission, behavior and self-perception about risk of getting HIV among men - Oli, NL; Onta, SR; Dhakal, S (Journal of Institute of Medicine Nepal, 2013)
Introduction: In spite on a lot of work done by nongovernmental organizations of men having sex with men (MSM) with the collaboration of Nepal government there is high prevalence of unprotected anal sex with a high incidence of sexual partner change. The purpose of this study was to explore knowledge about Human Immunodeficiency Virus (HIV) transmission, behavior and self-perception about risk of getting HIV among men having sex with men in Kathmandu Valley. Methods: This is cross-sectional explorative study. Study was carried out between July 2010 and December 2010 in 97 men having sex with men in Kathmandu Valley using snow balling sampling technique. The verbal consent was taken and the respondents were interviewed using structured questionnaire. Results: Although overall knowledge regarding HIV/AIDS and Sexual transmitted Infections (STI) is high some misconception about way of transmission is present. Majority of respondents still practiced unsafe sexual behaviors, which included multiple sex partners, irregular use of condom, frequent and regular anal sex, sex in exchange of money. More than half of them considered that they had little risk of getting HIV/AIDS. Conclusion: Sexual behavior of men having sex with men needs to be further addressed in order to promote safer and responsible sexual behavior. DOI: http://dx.doi.org/10.3126/joim.v34i2.9043 Journal of Institute of Medicine August, 2012; 34:2 4-9